Evaluación de la Contaminación Acústica mediante la Elaboración de Mapas Temáticos en el Centro Urbano de la Ciudad de Riobamba - Ángel Andres, Naranjo Polo (2020)
The research`s objective is to evaluate noise pollution in Riobamba’s historic city centre by developing thematic maps. The research approach is qualitative and quantitative, through a survey, citizen perception (qualitative) was captured to delimit the study area and designate 25 priority points for noise monitoring (quantitative) in the so-called historical centre. The results were interpreted by mean of thematic maps done with the ordinary Kringing geostatistical method. It was observed that the sites with the highest weighted equivalent limit are between a range of 60 and 80 Leq (A) that generates an ear sensation of uncomfortable background noises for conversations. The sites with the highest noise pollution are the Santa Rosa, La Joya, La Merced and Ferroviaria neighborhoods, which maintain a high level of noise in all the analyzed days. The analysis showed a notable noise increase on Saturday, and La Merced as the sector with the highest Leq (A) registered during the sampling days. It is recommended that monitoring system be applied throughout the Riobamba city. Based on that, the authorities could take decisions that reduce risks of possible permanent damage to the ear by long-term exposures to the inhabitants and bystanders.